GAMBARAN PENGETAHUAN MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI TENTANG GLAUKOMA - Theja, Andri; Sumual, Vera; Tongku, Yamin (e-CliniC, 2016)
Abstract: This study aimed to determine the knowledge about glaucoma of students of Faculty of Medicine, University of Sam Ratulangi Manado. This was a descriptive survey study by using questionnaire. This study was conducted at the Faculty of Medicine, University of Sam Ratulangi from October 2015 until December 2015. There were 81 respondents. Respondents were obtained by stratified random sampling in each batch, and in each batch we used simple random sampling. The results showed that the knowledge categories of students about glaucoma were as follows: moderate category in 57 respondents (70.4%), good category in 2 respondents (2.4%), and poor category in 22 respondents (27.2%). Conclusion: In this study, most of the students of Faculty of Medicine, University of Sam Ratulangi Manado had moderate category of knowledge about glaucoma. Keywords: glaucoma, student knowledgeÂ Abstrak: Penelitian ini bertujuan untuk mengetahui pengetahuan mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi tentang glaukoma. Jenis penelitian yang dilakukan ialah survei deskriptif, dengan membagikan kuesioner pengetahuan kepada responden. Penelitian ini dilakukan di Fakultas Kedokteran Universitas Sam Ratulangi sejak bulan Oktober sampai Desember 2015 dengan responden sebanyak 81 orang. Responden diperoleh berdasarkan teknik stratified random sampling pada masing-masing angkatan, kemudian untuk pengambilan sampel di tiap angkatan digunakan teknik simple random sampling. Hasil penelitian memperlihatkan kategori pengetahuan mahasiswa sebagai berikut: pengetahuan kategori sedang sebanyak 57 responden (70,4%), kategori baik sebanyak 2 responden (2,4%) dan kategori kurang sebanyak 22 responden (27,2%). Simpulan: Dalam penelitian ini, sebagian besar mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi mempunyai pengetahuan mengenai glaukoma dengan kategori sedang.Kata kunci: glaukoma, pengetahuan mahasiswa